HUKUM PAJAK DAN PENERAPANNYA UNTUK KESEJAHTERAAN SOSIAL - Agustina, Enny (Solusi, 2020)
Tax is one of the economic instruments of a country. Some taxes as a source of national income account for more than 50% of national income. This study uses a qualitative research method with a literature approach (normative). The data obtained comes from several regulations, such as Governor Regulations and several other regulations and policies. When a country has a higher income than taxes, there will be more jobs available, unemployment can be reduced, education is better, health services can be achieved. Taxes are also good instruments for income distribution. Meanwhile, income distribution is the biggest problem in today's economy.